Nutritious or Delicious? A survey demonstrating the impact of hunger and health behaviors on food preferences. (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
Unhealthy eating habits involving the consumption of highly-palatable energy-dense foods are a major contributor to weight gain its associated health conditions. Consumption of these “unhealthy” items continues to be common despite ongoing efforts for promoting healthy-eating behavior. However, relatively little is known about the factors that lead to the consumption of unhealthy foods. Prior research has shown that states of hunger influence the desire to eat without changing the perception or enjoyment of food items. The present study utilized an online-survey which asked participants to rate foods according to the items’ palatability, likelihood of being consumed, and healthiness. Demographic and bodily state information was also collected. The results of this study demonstrate that, in college students, a state of hunger biases the selection (“wanting”) of foods toward highly-palatable (“tasty”) food items. However, this finding was not observed in data gathered from a sample of older adults affiliated with a health and fitness organization. Collectively, this may suggest that age, education, or increased health-awareness can influence the preference for high-palatable foods that occurs when individuals are hungry.